2022
DOI: 10.5624/isd.20220078
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based apical lesion segmentation from panoramic radiographs

Abstract: Purpose Convolutional neural networks (CNNs) have rapidly emerged as one of the most promising artificial intelligence methods in the field of medical and dental research. CNNs can provide an effective diagnostic methodology allowing for the detection of early-staged diseases. Therefore, this study aimed to evaluate the performance of a deep CNN algorithm for apical lesion segmentation from panoramic radiographs. Materials and Methods A total of 1000 panoramic images sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The F1 score values were 82%, 81% and 74%, respectively, with IOU thresholds of 0.3, 0.4 and 0.5. The study demonstrated the ability of the deep learning‐guided method to segment apical lesions [41]. Also, Hamdan et al indicated that DL improved the ability of dental professionals to detect apical radiolucencies on intraoral periapical radiographs [42].…”
Section: Application Of Ai In Periapical Lesions Detection In Endodon...mentioning
confidence: 99%
“…The F1 score values were 82%, 81% and 74%, respectively, with IOU thresholds of 0.3, 0.4 and 0.5. The study demonstrated the ability of the deep learning‐guided method to segment apical lesions [41]. Also, Hamdan et al indicated that DL improved the ability of dental professionals to detect apical radiolucencies on intraoral periapical radiographs [42].…”
Section: Application Of Ai In Periapical Lesions Detection In Endodon...mentioning
confidence: 99%
“…Song et al [23] aimed to evaluate the performance of deep learning models based on CNNs (Convolutional Neural Networks) for apical lesion segmentation from panoramic radiographs. They trained a U-Net on a dataset consisting of 1000 radiographs in total.…”
Section: F Machado Et Almentioning
confidence: 99%
“…For apical lesion segmentation from panoramic radiographs, [20] adopts a deep learning technique. There were a total of 1691 images utilized for segmentation.…”
Section: Related Workmentioning
confidence: 99%